Long-term effects of neonicotinoids on reproduction and offspring development in the copepod Acartia tonsa. (November 2022) - Picone, Marco; Distefano, Gabriele Giuseppe; Marchetto, Davide; Russo, Martina; Baccichet, Marco; Brusò, Luca; Zangrando, Roberta; Gambaro, Andrea; Volpi Ghirardini, Annamaria
Abstract: Neonicotinoids (NEOs) are neurotoxic pesticides acting as nicotinic acetylcholine receptor agonists. NEOs' efficacy against pest insects has favoured their spreading use in agriculture, but their proven effectiveness against non-target insects in terrestrial and aquatic ecosystems also raised concern over their environmental impact. Crustaceans were often studied for the impacts of NEOs due to their economic values and nervous' system similarity with insects. However, most studies on crustaceans focused on acute effects or exposure of early-life stages, while long-term effects were seldom explored. The present study aimed to assess the potential long-term effects of four commercially available NEOs on the reproduction and offspring of the calanoid copepod Acartia tonsa, a key species in the food webs of several coastal and estuarine environments. NEOs were confirmed as potent interferents of copepod reproduction. The first-generation compound acetamiprid significantly inhibited egg production and hatching ratio at 10 ng L −1, while larval survival and development were affected at 81 ng L −1 . Similarly, the first-generation compound thiacloprid significantly inhibited the hatching ratio and larval development at 9 ng L −1, while it did not affect egg production and larval survival. Second-generation compounds were less toxic than acetamiprid and thiacloprid: clothianidin affected significantly only larval development of the offspring at 62 ng L −1, while thiamethoxam was not toxic at both the tested concentrations (8 ng L −1 and 84 ng L −1 ). These data evidenced that effects on copepods may occur at concentrations below the chronic aquatic life benchmarks reported by USEPA for acetamiprid (2100 ng L −1 ) and thiacloprid (970 ng L −1 ), suggesting that long-term effects of NEOs have been underestimated. A comparison with environmental concentrations evidenced that NEO-mediated effects on copepods are more liable in coastal areas receiving discharge from wastewater treatment plants or diffuse inputs from agricultural land during pesticide application periods. Highlights: Neonicotinoids are potent interferents of copepods' reproduction and offspring development. First-generation compounds acetamiprid and thiacloprid were the most toxic toward Acartia tonsa . Acetamiprid inhibited egg production, hatching, larval survival and larval development. Thiacloprid impaired significantly inhibited hatching and larval development. Clothianidin affected only larval development.